Genetic and non-genetic parameters of grower and layer performances in CARI-Sonali chicken - DAS, ANANTA KUMAR; KUMAR, SANJEEV; RAHIM, ABDUL; KOKATE, LAXMIKANT SAMBHAJI (The Indian Journal of Animal Sciences, 2017)
CARI-Sonali day-old chicks (437) were investigated to estimate genetic and non-genetic parameters of its grower and layer performance traits. Sex and hatch-differences were significant in the least squares means of chick weight, body weights at different ages, age at first egg and egg production. The regression effects of chick weight and housing weight were significant for body weights, age at first egg and egg weights. The chick weight and housing weight had negative phenotypic correlation (rP) with age at first egg and positive rP with other layer traits. Age at first egg had positive rP with egg weights and negative rP with egg production. This information might be useful for adopting suitable breeding strategy.